A nano-aluminum-based composite material welding wire and a preparation method thereof

CN122938482APending Publication Date: 2026-10-20MCC KUNYUAN (CHONGQING) METAL MATERIALS RESEARCH INSTITUTE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611248253.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-18
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0004]从目前的技术来看,纳米铝基复合材料焊丝极难高质量稳定制备,主要原因是焊丝中的纳米增强体难以有效调控及其诱导的加工难题,体现在:一是满足目标分布特征的纳米铝基锭坯需要根据纳米增强体的凝固特征进行针对性设计;二是焊丝成品线径仅为φ1.2mm,需经塑性变形减径获得,满足纳米增强体目标分布的变形路径难以制定;三是7xxx系等超高强纳米铝基复合材料强度高、塑性差、加工窗口窄,焊丝制备过程中极易开裂、断丝,塑性成形与热处理难以协同

Benefits of technology

本申请提供的纳米铝基复合材料焊丝的制备方法,通过熔铸工序中熔铸冷却速度的可调实现纳米增强体初始分布的控制,通过挤压工序中挤压比和挤压出料速度的可调实现纳米增强体条带分布特征的控制,通过拉拔工序中温热单拉与退火循环的小变形量、非再结晶退火实现条带分布特征的遗传,构成了从“初始分布”到“条带形成”再到“条带遗传”的调控路径,实现了纳米增强体在焊丝内部的定向调控。由于熔铸冷却速度决定了锭坯晶粒尺寸,晶粒尺寸决定了晶界处纳米增强体的初始分布状态,单次热挤压的挤压比和挤压出料速度共同决定了条带的长度、宽度与间隔,温热单拉的小变形量确保条带不被过度破坏,退火不发生再结晶使条带特征得以保留,由此改善了相关技术中纳米增强体难以有效调控及其诱导的开裂、断丝等加工难题,为纳米铝基复合材料焊丝产品的高品质制备提供了新的思路和方法。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This application belongs to the field of aluminum-based alloy technology, specifically disclosing a nano-aluminum-based composite welding wire and its preparation method. The preparation method includes: a casting process, in which a round bar ingot containing nano-reinforcements is prepared by casting, and the casting cooling rate is adjusted based on the target grain size of the solidification structure to form an initial distribution of nano-reinforcements in the round bar ingot; an extrusion process, in which the round bar ingot is formed into a wire blank by single hot extrusion, and the extrusion ratio and extrusion speed are adjusted based on the target distribution characteristics of the nano-reinforcement strips in the welding wire to form nano-reinforcement strips along the length of the wire blank; and a drawing process, in which the wire blank is reduced to the finished wire diameter using a hot single-drawing and annealing cycle drawing process, and the nano-reinforcement strips are inherited by the finished welding wire. This application achieves directional control of the nano-reinforcements inside the nano-aluminum-based composite welding wire, improving the difficulty in effectively controlling nano-reinforcements and the processing problems they induce.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of aluminum-based alloy technology, and in particular to a nano-aluminum-based composite welding wire and its preparation method. Background Technology

[0002] With the upgrading of equipment in high-end fields such as aerospace, rail transportation, and new energy, higher requirements are placed on the lightweight, high performance, and reliability of systems. Key components are made of high-performance aluminum alloys such as the 7xxx series, with complex topological spatial structures, and are manufactured using welding or even additive manufacturing processes. This creates an urgent need for high-performance aluminum alloy welding wires for welding and arc additive manufacturing. However, high-strength and high-toughness aluminum alloys such as the 7xxx series have a wide two-phase region, making them prone to hot cracking during the welding and arc additive manufacturing process. Ordinary welding wires are insufficient for achieving high-reliability welding or additive manufacturing.

[0003] In recent years, nanotechnology has been introduced into processes such as welding and arc additive manufacturing, and nano-aluminum matrix composites have come into focus as filler welding wires. The nano-reinforcing phase not only improves the mechanical properties of the matrix material but also strongly influences and improves grain growth and second-phase formation during solidification, suppressing the formation of solidification cracks during welding and additive manufacturing. Therefore, welding wires prepared using nano-aluminum matrix composites enable the welding and arc additive manufacturing of high-strength and high-toughness aluminum alloys such as the 7xxx series.

[0004] From a current technological perspective, the high-quality and stable preparation of nano-aluminum matrix composite welding wire is extremely difficult. The main reasons are the difficulty in effectively controlling the nano-reinforcing components within the wire and the resulting processing challenges. These challenges manifest in several ways: First, the nano-aluminum matrix ingot required to meet the target distribution characteristics needs to be specifically designed based on the solidification characteristics of the nano-reinforcing components. Second, the finished welding wire has a diameter of only φ1.2mm, requiring plastic deformation to reduce its diameter, making it difficult to determine the deformation path that satisfies the target distribution of the nano-reinforcing components. Third, ultra-high-strength nano-aluminum matrix composites such as the 7xxx series have high strength, poor plasticity, and a narrow processing window, making them prone to cracking and breakage during wire preparation, and hindering the coordinated application of plastic forming and heat treatment. Therefore, the distribution control of nano-reinforcing components in high-performance aluminum-based welding wires, represented by 7xxx series nano-aluminum matrix composite welding wires, is a significant bottleneck restricting their high-quality and stable preparation and application. Summary of the Invention

[0005] In view of the shortcomings of the prior art described above, the purpose of this application is to provide a nano-aluminum-based composite welding wire and its preparation method, so as to realize the directional control of the nano-reinforcement inside the welding wire and improve the processing problem caused by the difficulty in effectively controlling the nano-reinforcement and its induction during the preparation of nano-aluminum-based composite welding wire.

[0006] To achieve the above objectives, this application provides the following technical solution: a method for preparing a nano-aluminum-based composite welding wire, comprising: a casting process, wherein a round bar ingot containing nano-reinforcement is prepared by casting, and the casting cooling rate is adjusted based on the target grain size of the solidification structure to form an initial distribution of nano-reinforcement in the round bar ingot; an extrusion process, wherein the round bar ingot is formed into a wire blank by single hot extrusion, and the extrusion ratio and extrusion discharge speed are adjusted based on the target distribution characteristics of the nano-reinforcement strips in the welding wire to form nano-reinforcement strips along the length direction of the wire blank; and a drawing process, wherein the wire blank is reduced to the finished wire diameter by a hot single drawing and annealing cycle, and the nano-reinforcement strips are inherited to the finished welding wire.

[0007] In the above preparation method, the casting process controls the grain size of the solidified structure by adjusting the casting cooling rate. Utilizing the solidification characteristic of nano-reinforcements being pushed forward by the solid-liquid interface front and enriched at grain boundaries during solidification, the nano-reinforcements form an initial distribution pattern along the grain boundary network in the round bar billet. This initial distribution pattern provides the basis for the formation of strips in the subsequent extrusion process. In the extrusion process, the nano-reinforcements at the grain boundaries in the round bar billet are elongated and broken along the extrusion direction under the action of metal plastic rheology, forming nano-reinforcement strips along the length of the wire rod. By adjusting the extrusion ratio and extrusion discharge speed, the distribution characteristics such as the length, width, and spacing of the strips can be controlled. In the drawing process, a warm single-drawing and annealing cycle drawing process is adopted. In each cycle, the deformation per pass is small, and recrystallization does not occur during annealing. Only a slight elongation of the nano-reinforcement strip length and a slight decrease in the strip spacing width occur, thus preserving the distribution characteristics of the nano-reinforcement strips formed in the extrusion process and inheriting them into the finished welding wire.

[0008] Optionally, in the casting process, the nano-reinforcement satisfies at least one of the following characteristics (11) to (14): (11) the nano-reinforcement includes at least one of carbides, nitrides, borides or oxides; (12) the nano-reinforcement is a nanoparticle with a size of 20 nm to 300 nm; (13) the volume fraction of the nano-reinforcement in the round bar billet is less than or equal to 3%; (14) the nano-reinforcement is distributed at the grain boundaries during solidification.

[0009] Optionally, in the casting process, the diameter of the round bar billet is 30 mm to 80 mm.

[0010] Optionally, in the casting process, the casting cooling rate is adjusted based on the target grain size of the solidification structure, including: within a preset grain size range of the round bar billet, if the average grain size of the round bar billet increases, the casting cooling rate is reduced.

[0011] Optionally, if the average grain size of the round bar ingot is 40 μm to 70 μm, the melting and casting cooling rate is 10 to 50 ℃ / s; if the average grain size of the round bar ingot is 120 μm to 180 μm, the melting and casting cooling rate is 1 to 10 ℃ / s; if the average grain size of the round bar ingot is 200 μm to 300 μm, the melting and casting cooling rate is less than or equal to 1 ℃ / s.

[0012] Optionally, the extrusion process is performed in accordance with at least one of the following requirements (21) to (25): (21) the extrusion temperature is 400℃±5℃; (22) the extrusion ratio is 10 to 50; (23) the extrusion discharge speed is less than or equal to 30mm / s, and the control deviation of the extrusion discharge speed is 2mm / s; (24) the extrusion ratio and extrusion discharge speed are adjusted based on the target distribution characteristics of the nano-reinforcement strips in the welding wire, including: within the preset average length range, preset average width range and preset average interval range of the nano-reinforcement strips, if the average length of the nano-reinforcement strips increases, the average width decreases, and the average interval narrows, then the extrusion ratio is increased and the extrusion discharge speed is increased; (25) the diameter of the extruded wire blank is 3mm to 8mm.

[0013] Optionally, the drawing process includes: heating the wire blank to the temperature deformation range; reducing the diameter of the heated wire blank by drawing deformation in one pass; annealing after drawing deformation; and repeating the drawing deformation and annealing until the diameter is reduced to the finished wire diameter.

[0014] Optionally, the drawing process shall be performed in accordance with at least one of the following requirements (31) to (35): (31) the warm drawing temperature is 180°C to 200°C, and the temperature control accuracy is less than or equal to 3°C; (32) in each cycle, the deformation per pass shall be performed in accordance with the following requirements: if the wire diameter of the wire blank is greater than or equal to 3.8 mm, the compression per pass shall be less than or equal to 18%; if the wire diameter of the wire blank is greater than 2.6 mm and less than 3.8 mm, the compression per pass shall be less than or equal to 15%; if the wire diameter of the wire blank is less than or equal to 3.8 mm, the compression per pass shall be less than or equal to 15%; if the wire diameter of the wire blank is less than or equal to 3.8 mm, the compression per pass shall be less than or equal to 15%. 2.6mm, then the compression amount per pass is less than or equal to 12%; (33) During each cycle, the drawing speed shall be performed in accordance with the following requirements: if the wire diameter of the wire blank is greater than or equal to 3.8mm, then the drawing speed is less than or equal to 0.5m / s; if the wire diameter of the wire blank is less than 3.8mm, then the drawing speed is less than or equal to 0.8m / s; (34) if the wire diameter of the wire blank is less than 1.9mm for the first time after drawing, then peeling treatment shall be performed; (35) The annealing temperature is 330℃±5℃, and after the heat preservation is completed, the furnace is cooled to room temperature.

[0015] Optionally, the preparation method further includes: homogenizing the round bar billet with heat treatment after the casting process and before the extrusion process.

[0016] Optionally, the preparation method further includes annealing the wire blank after the extrusion process and before the drawing process.

[0017] This application also provides a nano-aluminum-based composite welding wire, which is prepared by any of the above preparation methods, and the welding wire has multiple nano-reinforcing strips uniformly distributed along the length direction of the welding wire.

[0018] Optionally, the nano-aluminum-based composite welding wire is a 7xxx series aluminum alloy.

[0019] Optionally, the average length, average width, and average spacing of the nanoreinforcement strips satisfy any of the following sets of parameters: the first set of parameters is an average length of 1000 μm to 1200 μm, an average width of 4 μm to 6 μm, and an average spacing of 5 μm to 10 μm; the second set of parameters is an average length of 400 μm to 600 μm, an average width of 7 μm to 13 μm, and an average spacing of 10 μm to 30 μm; and the third set of parameters is an average length of 200 μm to 300 μm, an average width of 15 μm to 25 μm, and an average spacing of 50 μm to 70 μm.

[0020] The beneficial effects of this application are as follows: The method for preparing nano-aluminum-based composite welding wire provided in this application controls the initial distribution of nano-reinforcement through adjustable casting cooling rate in the casting process, controls the strip distribution characteristics of nano-reinforcement through adjustable extrusion ratio and extrusion discharge rate in the extrusion process, and inherits the strip distribution characteristics through small deformation and non-recrystallization annealing in the drawing process. This constitutes a regulatory path from "initial distribution" to "strip formation" and then to "strip inheritance," realizing the directional regulation of nano-reinforcement within the welding wire. Since the casting cooling rate determines the ingot grain size, and the grain size determines the initial distribution state of nano-reinforcement at the grain boundaries, the extrusion ratio and extrusion discharge rate of a single hot extrusion jointly determine the length, width, and spacing of the strips. The small deformation of the hot single extrusion ensures that the strips are not excessively damaged, and the absence of recrystallization during annealing preserves the strip characteristics. This improves the difficulty in effectively controlling nano-reinforcement and the processing problems such as cracking and wire breakage induced by it in related technologies, providing a new idea and method for the high-quality preparation of nano-aluminum-based composite welding wire products. Attached Figure Description

[0021] Figure 1 This is a metallographic characterization diagram of the distribution of nano-reinforcement strips inside the welding wire in Embodiment 1 of this application; Figure 2 This is a metallographic characterization diagram of the distribution of nano-reinforcement strips inside the welding wire in Embodiment 2 of this application; Figure 3This is a metallographic characterization diagram of the distribution of nano-reinforcement strips inside the welding wire in Embodiment 3 of this application; Figure 4 This is a scanning electron microscope (SEM) characterization diagram of the nano-reinforcement strips and the TiB2 nano-reinforcement within the strips in Example 1 of this application.

[0022] Figure 5 This is a schematic flowchart illustrating the preparation method of the nano-aluminum-based composite welding wire provided in the embodiments of this application. Detailed Implementation

[0023] The following specific examples illustrate the implementation of this application. Those skilled in the art can easily understand other advantages and effects of this application from the content disclosed in this specification. This application can also be implemented or applied through other different specific embodiments. Various details in this specification can also be modified or changed based on different viewpoints and applications without departing from the spirit of this application. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.

[0024] In this application, unless otherwise stated, the term "multiple" means two or more.

[0025] The character " / " indicates that the objects before and after it are in an "or" relationship. For example, A / B means: A or B.

[0026] The term "and / or" describes an association between objects, indicating that three relationships can exist. For example, A and / or B means: A or B, or A and B.

[0027] Before describing the technical solution of this application, some of the technical terms used in this application will be explained in detail. In this application, "warm single drawing" refers to the operation method of heating the wire blank to the warm deformation range and then completing one pass of drawing deformation through a drawing die to achieve diameter reduction. The "warm deformation range" refers to the deformation temperature range between room temperature cold deformation and high temperature hot deformation. In this application, the warm deformation range can be 180°C to 200°C. "Warm single drawing and annealing cycle" refers to the process method of performing an annealing treatment after each pass of warm single drawing to eliminate the work hardening generated by the drawing in that pass, and repeating the process of "one pass of warm single drawing plus one annealing" as a cycle unit.

[0028] In this application, "nano-reinforcement strips" refers to the strip-shaped enriched region formed by the dense aggregation of nano-reinforcement particles along the length of the wire blank or welding wire. In the metallographic structure, it appears as a black contrast strip extending along the length direction, and in the scanning electron microscope backscattered image, it appears as a bright white contrast enriched strip. "Distribution characteristic inheritance" means that the distribution characteristics (including the length, width, and spacing of the strips) of the nano-reinforcement strips formed in the extrusion process are not destroyed in the subsequent drawing and diameter reduction process, but are retained and continued into the finished welding wire. "Extrusion ratio" refers to the ratio of the cross-sectional area of ​​the blank before extrusion to the total cross-sectional area of ​​the finished product after extrusion. "Pass compression amount" refers to the compression rate of the cross-sectional area of ​​the wire blank in a single drawing pass. "Peeling treatment" refers to the surface treatment method of performing overall removal processing on the surface of the wire to remove the oxide layer, microcracks, and other defect layers on the surface of the wire.

[0029] With the development of high-end equipment manufacturing fields such as aerospace, rail transportation, and new energy, high-performance aluminum alloys such as the 7xxx series (Al-Zn-Mg-Cu series) are widely used in key load-bearing components. These components have complex shapes and are mostly formed and connected by welding or arc additive manufacturing, thus creating an increasingly urgent demand for high-performance aluminum alloy welding wires. However, high-strength and high-toughness aluminum alloys such as the 7xxx series have a wide two-phase region, making them prone to hot cracking defects during the welding and arc additive manufacturing process. Ordinary welding wires are unable to achieve high-reliability welding or additive manufacturing. Nano-aluminum matrix composite welding wires introduce nano-reinforcements into the welding wire matrix. During the welding and solidification process, the nano-reinforcements can influence and improve grain growth and the formation of the second phase, suppressing solidification crack defects, thus making high-reliability welding and arc additive manufacturing of high-strength and high-toughness aluminum alloys such as the 7xxx series possible.

[0030] The preparation of nano-aluminum matrix composite welding wire typically follows a general process of "casting to form a billet, extruding to form a wire, and drawing to reduce the diameter": first, a billet containing nano-reinforcements is obtained by casting; then, the billet is transformed into a wire blank through extrusion; finally, the wire blank is reduced to the finished wire diameter (usually around φ1.2mm) through multiple drawing passes. In this process, the initial distribution state of the nano-reinforcements in the billet, their morphological evolution during extrusion deformation, and their retention degree during drawing to reduce the diameter collectively determine the final distribution morphology of the nano-reinforcements inside the finished welding wire, which in turn determines the effect of the welding wire in refining grains and inhibiting hot cracking during welding.

[0031] However, in related technologies, the distribution of nano-reinforcements in each stage of the aforementioned process has not formed an effective control chain. First, in the casting stage, related technologies typically focus on the uniform dispersion of nano-reinforcements in the melt without controlling the casting cooling rate. The initial distribution morphology of nano-reinforcements in the ingot is uncontrollable and cannot provide a definite distribution starting point for subsequent deformation stages. Nano-aluminum-based ingots that meet the target distribution characteristics need to be specifically designed based on the solidification characteristics of nano-reinforcements, but this design is lacking in related technologies.

[0032] Secondly, in the deformation and diameter reduction stage, the finished welding wire diameter is only about φ1.2mm, requiring extensive plastic deformation to achieve the desired diameter reduction. It is difficult to determine the deformation path that satisfies the target distribution of nano-reinforcements. Related technologies either use a fixed extrusion ratio without considering the influence of extrusion parameters on the reinforcement distribution morphology, or employ a large amount of deformation per pass (e.g., a single-pass cold drawing deformation of 15% to 30%). The distribution morphology of the nano-reinforcements is repeatedly disturbed during this drastic deformation, making it difficult to retain any previously formed distribution characteristics in the billet during the diameter reduction process.

[0033] Furthermore, 7xxx series and other ultra-high strength nano-aluminum matrix composites exhibit high strength but poor plasticity and a narrow processing window, making them highly susceptible to cracking and wire breakage during drawing and diameter reduction. Coordination between plastic forming and heat treatment is difficult: reducing deformation to preserve reinforcement distribution increases the number of passes and accumulates work hardening, requiring frequent annealing; improper annealing temperature control leading to recrystallization disrupts the reinforcement distribution due to microstructural reconstruction; increasing deformation to improve efficiency significantly increases the probability of material cracking and wire breakage. These contradictions make the distribution control of nano-reinforcements in high-performance aluminum-based welding wires, represented by 7xxx series nano-aluminum matrix composite welding wires, a significant bottleneck restricting their high-quality, stable preparation and application.

[0034] To address the aforementioned problems, this application proposes a three-level control technology concept: first-level control of "melting and casting cooling rate → billet grain size → initial distribution of nano-reinforcement at grain boundaries"; second-level control of "extrusion ratio and extrusion rate of a single hot extrusion → length, width, and spacing of nano-reinforcement strips"; and third-level control of "small deformation amount and non-recrystallization drawing in warm single drawing and annealing cycles → inheritance of strip distribution characteristics". This establishes a control process of "initial distribution → strip formation → strip inheritance" throughout the entire process from billet to finished welding wire, achieving directional control of the nano-reinforcement inside the welding wire. The following describes each embodiment in conjunction with the accompanying drawings.

[0035] As a basic implementation method, see [link to relevant documentation]. Figure 5This application provides a method for preparing a nano-aluminum-based composite welding wire, which includes a casting process, an extrusion process, and a drawing process. In the casting process, a round bar ingot containing nano-reinforcements is prepared by casting, and the casting cooling rate is adjusted based on the target grain size of the solidification structure to form an initial distribution of nano-reinforcements in the round bar ingot. In the extrusion process, a single hot extrusion is used to form a wire blank from the round bar ingot, and the extrusion ratio and extrusion discharge speed are adjusted based on the target distribution characteristics of the nano-reinforcement strips in the welding wire to form nano-reinforcement strips along the length direction of the wire blank. In the drawing process, a hot single drawing and annealing cycle drawing process is used to reduce the diameter of the wire blank to the finished wire diameter, and the nano-reinforcement strips are inherited to the finished welding wire.

[0036] See Figure 5 The melting and casting process corresponds to step S101, which involves melting and casting to prepare round bar ingots. Specifically, after heating and melting the aluminum alloy matrix, nano-reinforcing materials are added to the melt, stirred evenly, and then poured into a circular casting mold. After solidification, a round bar ingot is obtained. During the melting and casting process, the melting and casting cooling rate is adjusted based on the target grain size of the solidified structure. That is, the cooling rate during solidification is changed by controlling the cooling conditions during casting (such as mold material, mold temperature, cooling method, etc.), thereby controlling the grain size of the solidified structure.

[0037] The mechanism by which the initial distribution of nano-reinforcements is regulated during the casting process is as follows: During the solidification of aluminum alloy, nano-reinforcements are pushed forward by the solid-liquid interface front and eventually accumulate at grain boundaries, forming an initial distribution morphology along a grain boundary network. The faster the cooling rate, the greater the solidification undercooling, the higher the nucleation rate, the finer the grains, the larger the grain boundary area, and the more diffuse the distribution of nano-reinforcements at the grain boundaries. Conversely, the slower the cooling rate, the lower the nucleation rate, the coarser the grains, the smaller the grain boundary area, and the higher the enrichment degree of nano-reinforcements at the grain boundaries. Therefore, by adjusting the casting cooling rate, the first-level regulation of the initial distribution of nano-reinforcements in the round bar ingot can be achieved.

[0038] See Figure 5 The extrusion process corresponds to a single hot extrusion step S103. Specifically, the round bar billet obtained from melting and casting is heated to the extrusion temperature and placed in the extrusion cylinder of the extrusion press. It is then subjected to a single extrusion deformation through the extrusion die to obtain a wire billet with a uniform diameter. During the extrusion process, the nano-reinforcement at the grain boundaries in the round bar billet is elongated and broken along the extrusion direction under the action of metal plastic rheology, forming nano-reinforcement strips along the length of the wire billet.

[0039] The mechanism by which the extrusion process controls the strip distribution characteristics is as follows: the extrusion ratio determines the amount of deformation; the larger the extrusion ratio, the more fully the grain boundary network is stretched along the extrusion direction, resulting in longer and narrower strips. The extrusion discharge rate affects the residence time and dynamic recovery degree of the metal in the deformation zone; the faster the extrusion discharge rate, the more obvious the material softening effect, improving plasticity and fluidity, which is beneficial for further strip extension and refinement. Therefore, by adjusting the extrusion ratio and extrusion discharge rate based on the target distribution characteristics of the nano-reinforcement strips in the welding wire, the second-level control of the nano-reinforcement strip distribution characteristics (strip length, strip width, and strip spacing) can be achieved.

[0040] See Figure 5 The drawing process corresponds to a single pass of warm drawing (S105) and an annealing step to eliminate work hardening (S106). Specifically, the extruded wire blank is heated to a warm deformation range (e.g., 180°C to 200°C), and then drawn through a drawing die to achieve diameter reduction in one pass. Subsequently, it is annealed at an annealing temperature (e.g., 330°C ± 5°C) to eliminate work hardening from that pass. This process is repeated with the single pass of warm drawing (S105) and the annealing step to eliminate work hardening (S106), i.e., the wire diameter is gradually reduced to the finished wire diameter through a cycle of warm drawing and annealing. During the cycle, it is determined whether the finished wire diameter has been reached. If not, the cycle returns to the single pass of warm drawing (S105) to continue. If the diameter has been reached, the finished welding wire is obtained by peeling, thus inheriting the strip distribution characteristics formed in the extrusion process into the finished welding wire.

[0041] The mechanism by which the strip is inherited in the drawing process is as follows: In each cycle, the deformation amount per pass is small, and the strip will not break or redistribute due to a single severe deformation; the annealing temperature is lower than the recrystallization temperature of the material, and only the recovery effect occurs during the annealing process, eliminating work hardening without recrystallization, and the structure does not reconstruct. Therefore, the nano-reinforcement strips will not be redistributed or destroyed, but only a small extension of the length of the nano-reinforcement strips and a slight reduction in the width of the strip spacing will occur, so that the strip distribution characteristics formed in the extrusion process can be retained and inherited into the finished welding wire.

[0042] This embodiment achieves initial distribution control through adjustable casting cooling rate, strip characteristic control through adjustable extrusion ratio and extrusion speed in a single hot extrusion, and strip characteristic inheritance through small deformation and non-recrystallization annealing in warm single drawing and annealing cycles. The three work together to achieve full-process directional control of nano-reinforcement from ingot to finished welding wire, which improves the difficulty in effectively controlling nano-reinforcement in nano-aluminum matrix composite welding wire and the processing problems it induces, reduces the probability of cracking and wire breakage during welding wire preparation, and provides a new idea and method for high-quality preparation of nano-aluminum matrix composite welding wire products.

[0043] In some embodiments, the nano-reinforcement in the above-described casting process is further defined. The nano-reinforcement includes at least one of carbides, nitrides, borides, or oxides. Specifically, carbides may include, for example, titanium carbide (TiC), silicon carbide (SiC), tungsten carbide (WC), zirconium carbide (ZrC), boron carbide (B4C), etc.; nitrides may include, for example, silicon nitride (Si3N4), aluminum nitride (AlN), etc.; borides may include, for example, titanium diboride (TiB2), niobium diboride (NbB2), etc.; and oxides may include, for example, alumina (Al2O3), zirconium oxide (ZrO2), titanium dioxide (TiO2), cerium oxide (CeO2), yttrium oxide (Y2O3), etc. The above-mentioned nano-ceramic particles all possess high melting points, high hardness, and good thermal stability, and exhibit suitable interfacial wettability with the aluminum matrix, making them suitable as reinforcing phases in aluminum-based composite materials.

[0044] The nanoreinforcement consists of nanoparticles with a size ranging from 20 nm to 300 nm. This size range ensures the nano-effects of the nanoreinforcement (grain refinement, dendrite growth suppression, and provision of heterogeneous nucleation sites, etc.), while reducing the probability of severe agglomeration problems caused by excessively small particles (less than 20 nm) and the weakening of the reinforcement effect caused by excessively large particles (greater than 300 nm). Within this size range, for example, nanoparticles with an average particle size of 100 nm can be selected, or nanoparticles with an average particle size close to the lower limit (e.g., around 30 nm) or close to the upper limit (e.g., around 250 nm) can be selected, all of which can meet the distribution requirements of being pushed by the solid-liquid interface front and enriched at the grain boundaries during solidification.

[0045] The volume fraction of nano-reinforcement in the round bar billet is ≤3%. Controlling the volume fraction of nano-reinforcement below 3% ensures a controllable distribution network at grain boundaries, preventing excessive agglomeration and reducing processing difficulties (such as extrusion cracking and wire breakage) caused by excessive reinforcement content. This achieves a balance between reinforcement effect and processing performance. For example, the volume fraction can be 1.5%, or lower or higher values ​​can be chosen based on the reinforcement requirements of the welding wire, such as 0.5%, 1%, 2%, 2.5%, or 3%, provided it does not exceed 3%.

[0046] During solidification, the nano-reinforcements are distributed at the grain boundaries. This is because the nano-reinforcements are pushed by the solid-liquid interface front during the solidification of the aluminum alloy, eventually accumulating at the grain boundaries and forming a grain boundary network. This distribution characteristic is a prerequisite for the formation of nano-reinforcement strips in the subsequent extrusion process: the nano-reinforcements at the grain boundaries are elongated and broken along the metal rheological direction during extrusion deformation, thereby forming a strip structure along the length of the wire rod.

[0047] In some embodiments, the billet size in the casting process is further limited: the diameter of the round bar billet is 30mm to 80mm. This diameter range is set by comprehensively considering the requirements of the extrusion ratio and the wire diameter of the drawn wire. If the billet diameter is too small (less than 30mm), it is difficult to obtain a sufficient extrusion ratio range in the subsequent extrusion process, and it is impossible to fully control the characteristics of the nano-reinforcement strips; if the billet diameter is too large (greater than 80mm), it is difficult to control the diameter of the wire after extrusion within a suitable range for drawing, and the extrusion equipment is overloaded. Within the above diameter range, combined with the target wire diameter of φ3mm to φ8mm in the extrusion process, a reasonable range of extrusion ratio of 10 to 50 can be obtained to ensure the effective formation of nano-reinforcement strips. For example, the billet diameter can be φ50mm, or it can be φ30mm or φ35mm closer to the lower limit, or φ70mm or φ80mm closer to the upper limit, etc.

[0048] In some embodiments, the method of adjusting the cooling rate in the casting process is further defined: adjusting the casting cooling rate based on the target grain size of the solidification structure includes: within a preset grain size range for the round bar billet, if the average grain size of the round bar billet increases, then the casting cooling rate is reduced. This adjustment rule conforms to the general law of metal solidification: the faster the cooling rate, the greater the undercooling, the higher the nucleation rate, and the finer the grains; conversely, the slower the cooling rate, the lower the nucleation rate, and the coarser the grains. Therefore, when a larger grain size is required, the casting cooling rate is reduced to allow the grains to grow sufficiently; when a smaller grain size is required, the casting cooling rate is increased to promote nucleation and grain refinement. Thus, by adjusting the cooling rate in relation to the grain size, the initial distribution of nano-reinforcement in the round bar billet can be effectively controlled. The limitation of the billet diameter and the cooling rate adjustment rule can be used individually or in combination.

[0049] In some embodiments, a specific correspondence between cooling rate and grain size is further provided: if the average grain size of the round bar ingot is 40 μm to 70 μm, the melting and casting cooling rate is high, for example, 10~50 °C / s; if the average grain size of the round bar ingot is 120 μm to 180 μm, the melting and casting cooling rate is medium, for example, 1~10 °C / s; if the average grain size of the round bar ingot is 200 μm to 300 μm, the melting and casting cooling rate is low, for example, less than or equal to 1 °C / s. The mechanisms of the three cooling rates are explained below.

[0050] When high cooling rates are used for casting, the supercooling during solidification is large, the nucleation rate is significantly increased, and the grains solidify before they have time to grow, thus obtaining a fine-grained structure with an average grain size of 40 μm to 70 μm. The fine-grained structure has large grain boundary areas, and the nano-reinforcements are more dispersed at the grain boundaries, resulting in a dense grain boundary network. This provides initial conditions for the formation of long, dense strips in the subsequent extrusion process.

[0051] When casting is performed at a moderate cooling rate, the nucleation rate and grain growth rate are in equilibrium, resulting in a medium-grained structure with an average grain size of 120 μm to 180 μm. The enrichment of nano-reinforcement at the grain boundaries is between that of fine and coarse grains.

[0052] When casting is performed at a low cooling rate, the undercooling is small, the nucleation rate is low, and the grains grow sufficiently, resulting in a coarse-grained structure with an average grain size of 200μm to 300μm. The grain boundary area in the coarse-grained structure is small, and the enrichment of nano-reinforcement at the grain boundaries is high, forming a relatively concentrated grain boundary network, which provides the initial conditions for the formation of short, thick, and sparse strips in the subsequent extrusion process.

[0053] The three cooling rates mentioned above can be achieved by selecting different casting mold materials and mold temperatures. The casting mold can be made of metals such as copper or steel, and different cooling conditions can be obtained by controlling the mold temperature during casting. For example, when using a steel mold, controlling the mold temperature at 400℃ achieves a low cooling rate, resulting in a coarse-grained structure with an average grain size of approximately 226 μm; controlling the mold temperature at 250℃ achieves a medium cooling rate, resulting in a medium-grained structure with an average grain size of approximately 127 μm; and controlling the mold temperature at 180℃ achieves a high cooling rate, resulting in a fine-grained structure with an average grain size of approximately 56 μm. In other words, with the same mold material, the lower the mold temperature, the higher the cooling rate and the finer the grains. By establishing a clear correspondence between cooling rate and grain size, three levels of control over the initial distribution of nano-reinforcement in the round bar billet are achieved, providing selectable initial conditions for the formation of different stripe distribution characteristics in subsequent extrusion processes.

[0054] In some embodiments, the process parameters of the extrusion process are further defined. The extrusion temperature is 400℃±5℃. This temperature range ensures that the material has sufficient plastic flowability during extrusion, reducing cracking or uneven microstructure caused by excessively low temperatures, while also reducing the probability of grain coarsening and interfacial reactions between the reinforcement and the matrix caused by excessively high temperatures.

[0055] The extrusion ratio ranges from 10 to 50. The extrusion ratio can be controlled by changing the number of extrusion die holes, which should not exceed 10. With a fixed billet diameter and wire rod diameter, a smaller number of die holes results in a larger deformation per die hole, leading to a higher extrusion ratio. For example, with a billet diameter of φ50mm and a wire rod diameter of φ5mm, the extrusion ratio is 10 when the number of die holes is 10, 25 when the number of die holes is 4, and 50 when the number of die holes is 2. This range of 10 to 50 provides ample room for deformation adjustment, allowing nano-reinforcement strips to form different lengths, widths, and spacing characteristics.

[0056] The extrusion discharge speed is less than or equal to 30 mm / s, and the control deviation of the extrusion discharge speed is 2 mm / s (i.e., ±2 mm / s). Controlling the extrusion discharge speed within 30 mm / s ensures sufficient flow stability of the metal in the deformation zone, reducing uneven deformation and strip breakage caused by excessive speed; limiting the control deviation to 2 mm / s ensures the repeatability and consistency of the extrusion process, making the control results of strip distribution characteristics stable and reproducible.

[0057] In some embodiments, during the extrusion process, the extrusion ratio and extrusion speed are adjusted based on the target distribution characteristics of the nano-reinforcement strips in the welding wire. This includes: within a preset range of average length, average width, and average spacing of the nano-reinforcement strips, if the average length of the nano-reinforcement strips increases, the average width decreases, and the average spacing narrows, then the extrusion ratio is increased, and the extrusion speed is increased. In other words, the extrusion speed is positively correlated with the extrusion ratio. This adjustment rule is based on the following technical principle: when the extrusion ratio increases, the deformation increases, the grain boundary network is stretched more fully along the extrusion direction, and the strip length increases while the width decreases; when the extrusion speed increases, the strain rate of the metal in the deformation zone increases, the driving force for dynamic recovery and recrystallization is enhanced, and the material is more prone to recovery or recrystallization softening under high extrusion ratio conditions, improving plasticity and fluidity, which is beneficial for further strip extension and refinement. Therefore, selecting a faster extrusion speed under high extrusion ratio conditions can result in a larger strip length, a smaller strip width, and a narrower strip spacing.

[0058] In some embodiments, the diameter of the extruded wire rod is 3 mm to 8 mm. This range ensures that the wire rod has sufficient cross-sectional dimensions for subsequent drawing processes to reduce the diameter in multiple passes, while matching the extrusion ratio range of 10 to 50 and the billet diameter range of 30 mm to 80 mm. For example, the wire rod diameter can be φ5 mm, or it can be φ3 mm near the lower limit or φ8 mm near the upper limit, etc.

[0059] The process parameters for the extrusion process described above can be used individually or in any combination. For example, a combination of extrusion temperature 400℃±5℃, extrusion ratio 25, extrusion discharge speed 20mm / s±2mm / s, and wire rod diameter φ5mm can be used simultaneously. By precisely controlling the extrusion parameters and optimizing the matching relationship between the parameters, the directional control of the distribution characteristics of the nano-reinforcement strips is achieved.

[0060] In some embodiments, the specific operational steps of the drawing process are further defined. The drawing process includes: heating the wire blank to a warm deformation range; reducing the diameter of the heated wire blank through one pass of drawing deformation; annealing after drawing deformation; and repeating the drawing deformation and annealing until the diameter is reduced to the finished wire diameter. First, the wire blank is heated to a warm deformation range, which can be, for example, 180°C to 200°C, i.e., the warm drawing temperature is 180°C to 200°C. This temperature range corresponds to the warm deformation range of 7xxx series aluminum alloys, within which the material exhibits good plasticity without significant grain growth. After heating the wire blank from room temperature to the warm deformation range, the temperature control accuracy is ≤3°C to maintain temperature stability and prepare for drawing deformation.

[0061] Secondly, the heated wire blank undergoes a single drawing pass to reduce its diameter, i.e., the process is as follows: Figure 5 The step S105, a single pass of warm-drawing, is shown. Specifically, the wire blank heated to the warm deformation range is passed through the die hole of the drawing die. Under the action of the drawing force, the cross-sectional size of the wire blank decreases and its length increases. The drawing deformation amount of each pass needs to be controlled within a small range. For example, it can be controlled by grading according to wire diameter: when the wire diameter is ≥3.8mm, the pass compression amount is ≤18%; when the wire diameter is greater than 2.6mm and less than 3.8mm, the pass compression amount is ≤15%; when the wire diameter is ≤2.6mm, the pass compression amount is ≤12%. This grading control strategy is based on the following considerations: the finer the wire diameter, the higher the degree of work hardening of the material after cumulative deformation, and the lower the plasticity reserve. Therefore, the allowable pass deformation amount should be reduced accordingly. At the same time, the finer the wire diameter, the more sensitive the strip is to deformation disturbance. Reducing the pass compression amount is also conducive to the stable inheritance of strip distribution characteristics. By controlling the pass deformation amount by grading, the situation of material cracking or nano-reinforcement strip breakage caused by excessive single deformation amount is reduced.

[0062] Then, after drawing deformation, annealing is performed, i.e., the following process is carried out. Figure 5 The annealing process shown is step S106, which eliminates work hardening. An annealing regime can be, for example, annealing temperature 330℃±5℃, heating for 1~3 hours, holding for 1~3 hours, and furnace cooling to room temperature. This annealing temperature is lower than the material's recrystallization temperature. During annealing, only recovery occurs, eliminating work hardening caused by drawing deformation, without recrystallization. Therefore, the nano-reinforcement strips will not be redistributed or destroyed.

[0063] Finally, the drawing deformation and annealing operations are repeated until the diameter is reduced to the finished wire diameter. In each cycle, the deformation per pass is small, and no recrystallization occurs during annealing; only a slight increase in the length of the nano-reinforcement strips and a slight decrease in the strip spacing width occur. In a specific drawing process example, the wire blank starts at φ5.0mm, and after 22 drawing passes and 2 peeling processes, the diameter is gradually reduced to a finished wire diameter of φ1.185mm. The diameter changes for each pass are detailed in Table 1 below. In this drawing process, the area shrinkage rate of each pass is controlled within the limit range of the corresponding wire diameter range, and annealing is performed between adjacent passes to ensure the smooth progress of the drawing process and the inheritance of strip distribution characteristics.

[0064] By using the above-mentioned hot single-drawing and annealing cycle drawing process, the effective diameter reduction of the wire blank is achieved, and the distribution characteristics of the nano-reinforcement strips are not destroyed during the diameter reduction process. Ultimately, the strip characteristics are inherited into the finished welding wire, while reducing the probability of cracking and wire breakage of ultra-high strength nano-aluminum matrix composites such as 7xxx series during the diameter reduction process.

[0065] In some embodiments, the process parameters for the drawing process are further defined. During each cycle, the drawing speed is as follows: if the wire diameter is ≥3.8mm, the drawing speed is ≤0.5m / s; if the wire diameter is <3.8mm, the drawing speed is ≤0.8m / s. For thicker wire diameters, the deformation per pass is relatively large; using a lower drawing speed can reduce temperature rise and cracking caused by large deformation and excessive speed. For thinner wire diameters, the deformation per pass has been reduced according to the grading rules, allowing for a slightly higher drawing speed to improve production efficiency while ensuring quality.

[0066] If the wire diameter of the drawn wire blank is less than 1.9 mm for the first time, a stripping process is performed. The reason for setting this stripping time is that when the wire diameter is drawn to less than 1.9 mm, the cumulative deformation of the wire is already large, and defects such as oxide layers and microcracks may appear on the surface. At this time, the stripping process can remove the surface defect layer, which is conducive to the stability of subsequent drawing and helps to ensure the surface quality of the final welding wire. In the drawing process shown in Table 1 below, the wire diameter after the 15th drawing pass is φ1.84 mm, which is less than φ1.9 mm for the first time, so a stripping process is arranged (φ1.84 mm stripped to φ1.80 mm); in addition, after the last drawing pass (φ1.23 mm), a final stripping process (φ1.23 mm stripped to φ1.185 mm) is performed again to obtain the finished welding wire.

[0067] In some embodiments, the above preparation method may further include a homogenization heat treatment step, corresponding to Figure 5The homogenization heat treatment step S102 involves performing a homogenization heat treatment on the round bar billet after the casting process and before the extrusion process. The purpose of homogenization heat treatment is to eliminate compositional segregation and microstructure inhomogeneity formed during the solidification process of the ingot. Due to the presence of nano-reinforcement, the cooling conditions during ingot solidification are more complex, and compositional segregation and microstructure inhomogeneity may be more pronounced. If extrusion deformation is performed directly, localized compositional and microstructure differences may lead to uneven deformation or even cracking. The specific regime for homogenization heat treatment can be selected according to the material system. For example, for nano-TiB2 particle-reinforced AA7075 aluminum matrix composites, the homogenization heat treatment regime can be: heating to 465℃ for 4 hours, holding at that temperature for 28 hours, then cooling in the furnace to 200℃, and finally air-cooling to room temperature. Through homogenization heat treatment, alloying elements are fully diffused, and the microstructure is homogenized, providing a uniform matrix structure for subsequent extrusion deformation.

[0068] In some embodiments, the above preparation method may further include an extrusion wire rod annealing process, corresponding to Figure 5 Step S104 of the extrusion wire rod annealing process: After the extrusion process and before the drawing process, the wire rod is annealed. The purpose of annealing the wire rod after extrusion is to eliminate work hardening caused by extrusion deformation, restore the plasticity of the material, and provide a suitable microstructure for the subsequent drawing process. The annealing regime can be, for example, as follows: annealing temperature 330℃±5℃, heating for 1~3 hours, holding for 1~3 hours, and furnace cooling to room temperature. This annealing temperature is lower than the recrystallization temperature, resulting only in a recovery process that eliminates internal stress and work hardening, while preserving the nano-reinforced strip structure formed by extrusion.

[0069] This application also provides a nano-aluminum-based composite welding wire, which is prepared using the preparation method of any of the foregoing embodiments, and has multiple nano-reinforcing strips uniformly distributed along the length of the wire. See also Figures 1 to 3 In the image, the black-contrast stripes represent the nano-reinforcement strips distributed within the aluminum alloy matrix. Unlike the uniformly dispersed or randomly agglomerated distribution found in traditional welding wires, the nano-reinforcement in this product exhibits a directional, strip-like distribution. Specifically, the nano-reinforcement strips are arranged parallel to the length (axial direction) of the welding wire, uniformly distributed across the wire's cross-section and length. The strips are composed of densely aggregated nano-reinforcement particles, with the aluminum alloy matrix separating the strips. This strip distribution is the result of the initial grain boundaries formed during the casting process being elongated and broken into strips during the extrusion process, and then inherited to the finished welding wire through a small-deformation, non-recrystallization annealing process.

[0070] The welding wire of this embodiment, through the directional distribution of nano-reinforcement strips, can more effectively exert the grain refinement and hot crack suppression effects of nano-reinforcement during the welding process, thereby improving the performance of the welded joint; at the same time, since the strip distribution characteristics can be obtained through the above-mentioned process, the welding wire can meet the needs of different welding scenarios with a defined internal microstructure.

[0071] In some embodiments, the welding wire is further specified as follows: the nano-aluminum-based composite welding wire is a 7xxx series aluminum alloy. 7xxx series aluminum alloys (Al-Zn-Mg-Cu series) are characterized by high strength and high hardness, and are the main materials selected for key structural components in aerospace, rail transportation, and other fields. Nano-aluminum-based composite welding wire with a 7xxx series aluminum alloy matrix can effectively suppress the formation of solidification cracks during welding, improving the reliability of the weld joint. For example, the matrix can be AA7075 aluminum alloy.

[0072] In some embodiments, the average length, average width, and average spacing of the nanoreinforcement strips satisfy any one of the following sets of parameters. The first set of parameters is: average length of 1000 μm to 1200 μm, average width of 4 μm to 6 μm, and average spacing of 5 μm to 10 μm. This set of parameters corresponds to a process combination of high cooling rate, fine grain ingot, large extrusion ratio (e.g., 50), and high extrusion speed (e.g., 27 mm / s) to obtain a slender, dense strip distribution.

[0073] The second set of parameters is: average length 400μm to 600μm, average width 7μm to 13μm, and average spacing 10μm to 30μm. This set of parameters corresponds to a process combination of medium cooling rate billet, medium extrusion ratio (e.g., 25), and medium extrusion discharge speed (e.g., 20mm / s) to obtain strip characteristics with medium length and medium density distribution.

[0074] The third set of parameters is: average length 200μm to 300μm, average width 15μm to 25μm, and average spacing 50μm to 70μm. This set of parameters corresponds to a process combination of low cooling rate coarse ingot blank with small extrusion ratio (e.g., 10) and low extrusion discharge speed (e.g., 15mm / s) to obtain short, thick, and sparse strip distribution characteristics.

[0075] The above three sets of parameters correspond to different strip distribution characteristics requirements and can be selected according to specific welding scenarios so that the welding wire of this embodiment can better adapt to different welding conditions and performance requirements.

[0076] The technical solution of this application is further illustrated below with specific examples. In all the examples below, the preparation object is AA7075 aluminum matrix composite welding wire reinforced with nano-TiB2 particles. The average particle size of the TiB2 nano-reinforcing particles is 100 nm, the designed volume fraction is 1.5%, the diameter of the round bar billet is φ50 mm, and the diameter of the wire billet is φ5 mm. In each example, the directional control effect of the strip distribution characteristics is verified by different combinations of melting and casting cooling rate, extrusion ratio, and extrusion discharge rate. It should be noted that "Example 1", "Example 2", and "Example 3" used in the following examples are only for comparison with Figures 1 to 4 The names of the figures are set to correspond, and do not imply that there is a difference in quality between the examples.

[0077] Example 1 This embodiment aims to prepare welding wire that meets the distribution characteristics of nano-reinforcement strips with an average length of 200 μm to 300 μm, an average strip width of 20 μm ± 5 μm, and an average strip spacing of 50 μm to 70 μm. The process flow is as follows: First, step S101, which involves melting and casting to prepare round bar ingots, is performed. AA7075 aluminum matrix composite ingots reinforced with nano-TiB2 particles are prepared using the melting and casting method. The average particle size of the TiB2 particles is 100 nm, and the designed volume fraction is 1.5%. A steel mold is used for casting at a temperature of 400℃. After casting, the ingots are air-cooled to room temperature at a melting and casting cooling rate of 0.1~0.5 ℃ / s. The diameter of the round bar ingot is φ50 mm, resulting in a coarse-grained structure with an average grain size of 226 μm.

[0078] Then, the homogenization heat treatment step S102 is performed to homogenize the ingot. The heat treatment regime is as follows: heat up to 465°C in 4 hours, hold for 28 hours and then cool down to 200°C in the furnace, and then remove and air cool to room temperature.

[0079] Next, a single hot extrusion step S103 is performed to obtain a wire blank with a wire diameter of φ5mm. The number of die holes in the extrusion die is 10, the extrusion ratio is 10, the extrusion temperature is 400℃±5℃, and the extrusion discharge speed is 15mm / s.

[0080] Then, the extrusion wire rod annealing step S104 is performed to anneal the extrusion wire rod. The annealing regime is as follows: annealing temperature 330℃±5℃, heating for 2 hours, holding for 2 hours, and cooling to room temperature in the furnace.

[0081] Finally, following the drawing process shown in Table 1, a cycle of warm single-pass drawing (S105) and annealing to eliminate hardening (S106) is performed to reduce the wire diameter to the finished wire diameter. The inter-pass annealing regime is as follows: annealing temperature 330℃±5℃, heating for 2 hours, holding for 2 hours, and furnace cooling to room temperature; warm drawing temperature is 180℃ to 200℃, with a temperature control accuracy of ≤3℃; after the 15th drawing pass, the wire diameter is φ1.84mm, which is the first time the wire diameter is less than φ1.9mm, so a peeling process is performed to reduce the wire diameter from φ1.84mm to φ1.80mm; thereafter, the drawing cycle continues until the finished wire diameter is reached, and then peeling is performed again to reduce the wire diameter from φ1.23mm to φ1.185mm to obtain the welding wire product.

[0082] Table 1. Drawing process of AA7075 aluminum matrix composite welding wire reinforced with nano-TiB2 particles

[0083] The metallographic structure of the finished welding wire obtained in Example 1 is as follows: Figure 1 As shown, the black contrasting stripes are nano-reinforcement strips, uniformly distributed along the length of the welding wire in the aluminum alloy matrix. The strips are short, thick, discrete, and spindle-shaped, with relatively wide stripes and large intervals. Statistically, the average strip length is 270 μm, the average strip width is 18 μm, and the average strip interval is 55 μm, meeting the target distribution characteristics of an average strip length of 200 μm to 300 μm, an average strip width of 20 μm ± 5 μm, and an average strip interval of 50 μm to 70 μm. Furthermore, the welding wire of Example 1 was characterized by scanning electron microscopy, and the results are as follows... Figure 4 As shown, it was verified that the strip contained densely aggregated TiB2 nanoparticles, and that the strip was highly oriented and extended continuously along the extrusion and drawing direction.

[0084] Example 2 This embodiment aims to prepare welding wire that meets the distribution characteristics of nano-reinforcement strips with an average length of 400 μm to 600 μm, an average strip width of 10 μm ± 3 μm, and an average strip spacing of 10 μm to 30 μm. The process flow is as follows: First, step S101, which involves melting and casting to prepare round bar ingots, is performed. AA7075 aluminum matrix composite ingots reinforced with nano-TiB2 particles are prepared using the melting and casting method. The average particle size of the TiB2 particles is 100 nm, and the designed volume fraction is 1.5%. A steel mold is used for casting at a temperature of 250℃. After casting, the ingots are air-cooled to room temperature at a melting and casting cooling rate of 6~8 ℃ / s. The diameter of the round bar ingot is φ50 mm, resulting in a medium-sized grain structure with an average grain size of 127 μm.

[0085] Then, the homogenization heat treatment step S102 is performed. The heat treatment regime is as follows: heat up to 465°C in 4 hours, hold for 28 hours, cool down to 200°C in the furnace, and then air cool to room temperature.

[0086] Next, a single hot extrusion step S103 is performed to obtain a wire blank with a wire diameter of φ5mm. The number of die holes in the extrusion die is 4, the extrusion ratio is 25, the extrusion temperature is 400℃±5℃, and the extrusion discharge speed is 20mm / s.

[0087] Then, the extrusion billet annealing step S104 is performed. The annealing regime is as follows: annealing temperature 330℃±5℃, heating for 2 hours, holding for 2 hours, and cooling to room temperature in the furnace.

[0088] Finally, the drawing process shown in Table 1 is performed in a cycle of warm single drawing step S105 and annealing to eliminate hardening step S106, reducing the diameter to the finished wire diameter, and then peeling to obtain the welding wire product. The annealing regime between passes is the same as in Example 1.

[0089] The metallographic structure of the finished welding wire obtained in Example 2 is as follows: Figure 2 As shown, the black contrasting stripes are nano-reinforcement strips, uniformly distributed along the length of the welding wire in the aluminum alloy matrix, and... Figure 1 Compared to the previous strips, the strips are significantly longer and thinner, with smaller intervals, and some strips are even joined end to end. Statistically, the average strip length is 580 μm, the average strip width is 9 μm, and the average strip interval is 22 μm, which meets the target distribution characteristics requirements of an average strip length of 400 μm to 600 μm, an average strip width of 10 μm ± 3 μm, and an average strip interval of 10 μm to 30 μm.

[0090] Example 3 This embodiment aims to prepare welding wire that meets the distribution characteristics of nano-reinforcement strips with an average length of 1000 μm to 1200 μm, an average strip width of 5 μm ± 1 μm, and an average strip spacing of 5 μm to 10 μm. The process flow is as follows: First, step S101, which involves melting and casting to prepare round bar ingots, is performed. AA7075 aluminum matrix composite ingots reinforced with nano-TiB2 particles are prepared using the melting and casting method. The average particle size of the TiB2 particles is 100 nm, and the designed volume fraction is 1.5%. A steel mold is used for casting at a temperature of 180℃. After casting, the ingots are air-cooled to room temperature at a melting and casting cooling rate of 35~45 ℃ / s. The diameter of the round bar ingot is φ50 mm, resulting in a fine-grained structure with an average grain size of 56 μm.

[0091] Then, the homogenization heat treatment step S102 is performed. The heat treatment regime is as follows: heat up to 465°C in 4 hours, hold for 28 hours, cool down to 200°C in the furnace, and then air cool to room temperature.

[0092] Next, a single hot extrusion step S103 is performed to obtain a wire blank with a wire diameter of φ5mm. The number of die holes in the extrusion die is 2, the extrusion ratio is 50, the extrusion temperature is 400℃±5℃, and the extrusion discharge speed is 27mm / s.

[0093] Then, the extrusion billet annealing step S104 is performed. The annealing regime is as follows: annealing temperature 330℃±5℃, heating for 2 hours, holding for 2 hours, and cooling to room temperature in the furnace.

[0094] Finally, the drawing process shown in Table 1 is performed in a cycle of warm single drawing step S105 and annealing to eliminate hardening step S106, reducing the diameter to the finished wire diameter, and then peeling to obtain the welding wire product. The annealing regime between passes is the same as in Example 1.

[0095] The metallographic structure of the finished welding wire obtained in Example 3 is as follows: Figure 3 As shown, the black contrast strips are nano-reinforcement strips, uniformly distributed in the aluminum alloy matrix along the length of the welding wire. The strips are thin, dense, and long, exhibiting a nearly continuous fibrous appearance that extends across the field of view, with their height parallel to the length of the welding wire. Statistically, the average strip length is 1080 μm, the average strip width is 4 μm, and the average strip spacing is 8 μm, meeting the target distribution characteristics requirements of an average strip length of 1000 μm to 1200 μm, an average strip width of 5 μm ± 1 μm, and an average strip spacing of 5 μm to 10 μm.

[0096] As can be seen from Examples 1 to 3, the three examples use the same material system (nano-TiB2 particle-reinforced AA7075 aluminum matrix composite material, TiB2 average particle size 100nm, volume fraction 1.5%), the same ingot diameter (φ50mm), the same wire diameter (φ5mm), the same homogenization heat treatment regime, the same annealing regime, and the same drawing process (Table 1). The only difference lies in the combination of three process variables: casting mold temperature (400℃, 250℃, 180℃) and the corresponding casting cooling rate (high cooling rate 35~45℃ / s, medium cooling rate 6~8℃ / s, low cooling rate 0.1~0.5℃ / s), the number of extrusion die holes (10, 4, 2) and the corresponding extrusion ratio (10, 25, 50), and the extrusion discharge speed (15mm / s, 20mm / s, 27mm / s). Thus, three welding wire products with different target distribution characteristics were obtained, and the measured results all fell within the target range. This indicates that the combination of melting and casting cooling rate, extrusion ratio and extrusion discharge rate is the key process variable that determines the distribution characteristics of nano-reinforcement strips in the finished welding wire. The three-level control method of this application can achieve on-demand directional acquisition of strip distribution characteristics.

[0097] Furthermore, the data patterns in the three examples above also show that if the combination of a large extrusion ratio and a high extrusion rate is deviated from the basis of a fine-grained billet (e.g., an average grain size of 56 μm), for example, only a small extrusion ratio is used, the dense grain boundary network cannot be sufficiently elongated, making it difficult to obtain long, thin strips with an average length of over 1000 μm. Conversely, if a large extrusion ratio and a high extrusion rate are forcibly used on the basis of a coarse-grained billet, although the sparse grain boundary network is elongated, the strip spacing is still constrained by the initial grain size, making it equally difficult to obtain the target dense strip distribution. In other words, there is a coordination relationship between the initial distribution determined by the casting cooling rate and the degree of deformation determined by the extrusion parameters. This application achieves the distribution control of nano-reinforcement in the wire rod through an appropriate combination of process (first-level control) and process (second-level control), and then achieves the inheritance of the distribution characteristics in the wire rod to the finished welding wire through process (third-level control).

[0098] In summary, the technical solution of this application achieves directional control of the nano-reinforcement strips inside the nano-aluminum matrix composite welding wire through the coordinated operation of three-level regulation of casting cooling rate, extrusion ratio and extrusion discharge rate, and hot single drawing and annealing cycle. This improves a series of problems in related technologies, such as uncontrollable initial distribution of nano-reinforcement, inability to transmit strip distribution characteristics, easy cracking and wire breakage during the drawing and diameter reduction process of 7xxx series ultra-high strength nano-aluminum matrix composites, and difficulty in coordinating plastic forming and heat treatment. It provides a feasible process path for the high-quality and stable preparation of nano-aluminum matrix composite welding wire products.

[0099] Those skilled in the art will understand that, without departing from the concept of this application, the specific implementation methods in the foregoing embodiments can be equivalently replaced or modified. For example, in addition to copper or steel, the material of the casting mold can also be other metallic materials whose cooling conditions can be controlled by the mold temperature; in addition to the carbides, nitrides, borides, and oxides listed above, other nanoparticles that can be enriched at grain boundaries and have considerable thermal stability during solidification can also be selected as nano-reinforcers; in addition to changing the number of extrusion die holes, the extrusion ratio can also be controlled by changing the ratio of the ingot diameter to the wire rod diameter, provided that the ingot diameter and wire rod diameter can be adjusted; all the above equivalent methods are within the scope of this application.

[0100] The above embodiments are merely illustrative of the principles and effects of this application and are not intended to limit this application. Any person skilled in the art can modify or alter the above embodiments without departing from the spirit and scope of this application. Therefore, all equivalent modifications or alterations made by those skilled in the art without departing from the spirit and technical concept disclosed in this application should still be covered by the claims of this application.

Claims

1. A method for preparing a nano-aluminum-based composite welding wire, characterized in that, include: In the melting and casting process, a round bar ingot containing nano-reinforcement is prepared by melting and casting, and the melting and casting cooling rate is adjusted based on the target grain size of the solidification structure so that the nano-reinforcement forms an initial distribution in the round bar ingot. In the extrusion process, the round bar billet is formed into a wire blank by single hot extrusion, and the extrusion ratio and extrusion speed are adjusted based on the target distribution characteristics of the nano-reinforcing strips in the welding wire, so that the initial distribution forms nano-reinforcing strips along the length direction of the wire blank. In the drawing process, a hot single drawing and annealing cycle drawing process is used to reduce the diameter of the wire blank to the finished wire diameter, and the nano-reinforcing strips are inherited to the finished welding wire.

2. The method for preparing the nano-aluminum-based composite welding wire according to claim 1, characterized in that, In the casting process, the nano-reinforcement satisfies at least one of the following characteristics (11) to (14): (11) The nano-reinforcement includes at least one of carbides, nitrides, borides or oxides; (12) The nano-reinforcement is a nanoparticle with a size of 20 nm to 300 nm; (13) The volume fraction of the nano-reinforcement in the round bar billet is less than or equal to 3%; (14) The nano-reinforcement is distributed at the grain boundaries during the solidification process.

3. The method for preparing the nano-aluminum-based composite welding wire according to claim 1, characterized in that, In the casting process, the diameter of the round bar billet is 30 mm to 80 mm; And / or, adjusting the casting cooling rate based on the target grain size of the solidification structure, including: reducing the casting cooling rate if the average grain size of the round bar billet increases within a preset grain size range of the round bar billet.

4. The method for preparing the nano-aluminum-based composite welding wire according to claim 3, characterized in that, In the casting process, adjusting the casting cooling rate based on the target grain size of the solidification structure includes: If the average grain size of the round bar ingot is 40 μm to 70 μm, then the melting and casting cooling rate is 10~50 ℃ / s; If the average grain size of the round bar ingot is 120 μm to 180 μm, then the melting and casting cooling rate is 1~10 ℃ / s; If the average grain size of the round bar ingot is 200 μm to 300 μm, then the melting and casting cooling rate is less than or equal to 1 °C / s.

5. The method for preparing the nano-aluminum-based composite welding wire according to claim 1, characterized in that, The extrusion process shall be performed in accordance with at least one of the following requirements (21) to (25): (21) The extrusion temperature is 400℃±5℃; (22) The extrusion ratio is 10 to 50; (23) The extrusion discharge speed is less than or equal to 30 mm / s, and the control deviation of the extrusion discharge speed is 2 mm / s; (24) Adjusting the extrusion ratio and extrusion speed based on the target distribution characteristics of the nano-reinforcing strips in the welding wire, including: within the preset average length range, preset average width range and preset average interval range of the nano-reinforcing strips, if the average length of the nano-reinforcing strips increases, the average width decreases and the average interval narrows, then the extrusion ratio is increased and the extrusion speed is increased. (25) The diameter of the extruded wire blank is 3 mm to 8 mm.

6. The method for preparing the nano-aluminum-based composite welding wire according to claim 1, characterized in that, The drawing process includes: The wire blank is heated to the temperature deformation range; The heated wire blank is subjected to a one-pass drawing deformation to reduce its diameter; Annealing is performed after the drawing deformation; Repeat the drawing deformation and annealing process until the diameter is reduced to the finished wire diameter.

7. The method for preparing the nano-aluminum-based composite welding wire according to claim 6, characterized in that, In the drawing process, at least one of the following requirements (31) to (35) shall be performed: (31) The temperature for hot drawing is 180℃ to 200℃, and the temperature control accuracy is less than or equal to 3℃; (32) During each cycle, the deformation per pass shall be performed in accordance with the following requirements: If the diameter of the wire blank is greater than or equal to 3.8 mm, the compression per pass is less than or equal to 18%. If the diameter of the wire blank is greater than 2.6 mm and less than 3.8 mm, then the compression per pass is less than or equal to 15%. If the diameter of the wire blank is less than or equal to 2.6 mm, the compression per pass is less than or equal to 12%. (33) During each cycle, the drawing speed shall be performed in accordance with the following requirements: If the diameter of the wire blank is greater than or equal to 3.8 mm, the drawing speed is less than or equal to 0.5 m / s; If the diameter of the wire blank is less than 3.8 mm, the drawing speed is less than or equal to 0.8 m / s; (34) If the wire diameter of the wire blank is less than 1.9 mm for the first time after drawing, then a peeling process shall be performed; (35) The annealing temperature is 330℃±5℃, and after the heat preservation is completed, the furnace is cooled to room temperature.

8. The method for preparing the nano-aluminum-based composite welding wire according to any one of claims 1 to 7, characterized in that, Also includes: After the melting and casting process and before the extrusion process, the round bar billet is subjected to homogenization heat treatment; And / or, after the extrusion process and before the drawing process, the wire blank is annealed.

9. A nano-aluminum-based composite material welding wire, characterized in that, Prepared by any one of claims 1 to 8, the welding wire has a plurality of nano-reinforcement strips uniformly distributed along the length direction of the welding wire.

10. The nano-aluminum-based composite welding wire according to claim 9, characterized in that, The nano-aluminum-based composite welding wire is a 7xxx series aluminum alloy; And / or, the average length, average width, and average spacing of the nanoreinforcement strips satisfy any one of the following sets of parameters: The first set of parameters is an average length of 1000 μm to 1200 μm, an average width of 4 μm to 6 μm, and an average spacing of 5 μm to 10 μm; The second set of parameters is an average length of 400 μm to 600 μm, an average width of 7 μm to 13 μm, and an average spacing of 10 μm to 30 μm; The third set of parameters is an average length of 200 μm to 300 μm, an average width of 15 μm to 25 μm, and an average spacing of 50 μm to 70 μm.